2013
DOI: 10.1371/journal.pone.0053120
|View full text |Cite|
|
Sign up to set email alerts
|

Olfactory Cues Are Subordinate to Visual Stimuli in a Neotropical Generalist Weevil

Abstract: The tropical root weevil Diaprepes abbreviatus is a major pest of multiple crops in the Caribbean Islands and has become a serious constraint to citrus production in the United States. Recent work has identified host and conspecific volatiles that mediate host- and mate-finding by D. abbreviatus. The interaction of light, color, and odors has not been studied in this species. The responses of male and female D. abbreviatus to narrow bandwidths of visible light emitted by LEDs offered alone and in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Thus, trap efficiency may be improved in the field by the addition of UV light, rather than relying completely on olfactory attractants. The importance of visual cues in monitoring has recently been studied in the tropical root weevil Diaprepes abbreviates L., which showed a hierarchy between chemo‐ and phototaxis, and used visual cues in short‐range host finding (Otalora‐Luna et al , ). A similar pattern of subordination of chemotaxis to phototaxis was shown in many Lepidoptera species (Shorey & Gaston, ; Balkenius et al , ; Goyret et al , ) and in the Colorado potato beetle Leptinotarsa decemlineata (Otalora‐Luna & Dickens, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, trap efficiency may be improved in the field by the addition of UV light, rather than relying completely on olfactory attractants. The importance of visual cues in monitoring has recently been studied in the tropical root weevil Diaprepes abbreviates L., which showed a hierarchy between chemo‐ and phototaxis, and used visual cues in short‐range host finding (Otalora‐Luna et al , ). A similar pattern of subordination of chemotaxis to phototaxis was shown in many Lepidoptera species (Shorey & Gaston, ; Balkenius et al , ; Goyret et al , ) and in the Colorado potato beetle Leptinotarsa decemlineata (Otalora‐Luna & Dickens, ).…”
Section: Discussionmentioning
confidence: 99%
“…Predominance of visual over olfactory cues was also reported for Vanessa indica (Lepidoptera: Nymphalidae) by Omura and Honda [37], who found that naive butterflies depended primarily on color and secondarily on scent during flower visitation. In one recent study that evaluated visual responses of the tropical root weevil Diaprepes abbreviatus (Coleoptera: Curculionidae) to light in the presence and absence of citrus volatiles, Otalora-Luna et al [38] documented that, in the absence of light, the addition of citrus volatiles to an air stream during the test period did not elicit an orientation response but the presence of lights elicited a strong weevil response.…”
Section: Discussionmentioning
confidence: 99%
“…Plant stimi used by insects as foraging cues are optical and chemical (i.e., volatile organic compounds [VOCs] and contact cues), and are often used in combination of both (Patt & Sétamou, ; Schoonhoven, van Loon, & Dicke, ; Vargas, Troncoso, Tapia, Olivares‐Donoso, & Niemeyer, ). Host odours are regarded as predominant cues initiating insect foraging behaviour and guiding their plant location, particularly in highly specialized insects (Otálora‐Luna, Lapointe, & Dickens, ). However, visual cues are essential for certain herbivorous insects (Stenberg & Ericson, ), and odours sometimes only enhance the insect response to visual cues (Patt & Sétamou, ).…”
Section: Introductionmentioning
confidence: 99%